Environmental, Social, and Governance (ESG) Reporting and Firm Value in Nigeria Manufacturing Firms: The Moderating Role of Firm Advantage - Igbinovia, Ikponmwosa Michael; Agbadua, Bamidele Oyakhiromhe (Jurnal Dinamika Akuntansi dan Bisnis, 2023)
The study examines the influence of environmental, social and governance (ESG) reporting on value-based performance; and the moderating effect of firm advantage on the nexus between ESG reporting and value-based performance of Nigerian quoted manufacturing firms. Using secondary data from the annual report of 20 manufacturing firms for the period 2017 to 2021, analysis involved descriptive statistics, correlation and regression analysis. The study finds that ESG reporting exerts no significant impact of firm value during the study period, but the effect was magnified and significant when moderated with firm advantage (profitability minus capital cost). Firm advantage has a significant effect on firm value-based performance of Nigerian quoted firms. No direct impact was observed for ESG and firm value, implying that ESG disclosures can only influence firm value meaningfully if it is focused on improving profitability by increasing sales through improved public image, and by achieving reduced finance cost. From the studys findings, ESG alone do not directly drive firm valuation, suggesting the existence of possible channels of transmitting ESG disclosure to value.